2008
DOI: 10.1007/s10722-008-9311-4
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite variability within and among local landrace populations of tea, Camellia sinensis (L.) O. Kuntze, in Kyoto, Japan

Abstract: Genetic variability within and among eight landrace populations of tea (Camellia sinensis (L.) O. Kuntze) located in southern Kyoto, Japan, was surveyed with six microsatellite markers. The average number of alleles per locus was 3.83 to 4.67 for landrace populations, whereas the corresponding value among modern cultivars and breeding lines was 6.63. Expected heterozygosity values averaged over loci within landrace populations ranged from 0.498 to 0.723. A similar level of variation, 0.682, was observed for cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 15 publications
1
16
1
Order By: Relevance
“…Results generated by STMSs data are generally in good agreement with the taxonomic classification and pedigree information (Savige 1993, Mondal et al 2002, Scariot et al 2006, Scariot et al 2007b, Tateishi et al 2007, Ohsako et al 2008, Caser and Scariot 2009). …”
Section: Genetic Diversitysupporting
confidence: 66%
See 1 more Smart Citation
“…Results generated by STMSs data are generally in good agreement with the taxonomic classification and pedigree information (Savige 1993, Mondal et al 2002, Scariot et al 2006, Scariot et al 2007b, Tateishi et al 2007, Ohsako et al 2008, Caser and Scariot 2009). …”
Section: Genetic Diversitysupporting
confidence: 66%
“…Most of the genetic diversity was attributable to differences within populations (66.47 % and 59.91 %), reflecting the extensive genetic variation mainly caused by the origin (breeding company) of the cultivars, which was observed in C. sinensis cultivars by Ohsako et al (2008).…”
Section: Genetic Diversitymentioning
confidence: 99%
“…A further explanation for these genetic diversity results could be that tea populations cultivated at the national level are derived from a similar gene pool and share a common genetic background. Lack of genetic differentiation among the populations has also been reported in earlier studies of tea (Wachira et al 1995(Wachira et al , 2001Paul et al 1997;Yao et al 2008;Ohsako et al 2008). Exchange of genetic material in cultivated crop species in most of the cases is dictated more by human intervention than by natural factors.…”
Section: Extent Of Genetic Variationmentioning
confidence: 52%
“…In the past decade or so, many efforts have been made to assess the genetic diversity of Indian tea germplasm at the phenotypic (Barua 1963;Banerjee 1992;Das 2001), cytogenetic (Bezbaruah 1971), biochemical (Saravanan et al 2005, and molecular levels (Paul et al 1997;Mondal 2002;Wachira et al 2001;Balasaravanan et al 2003;Singh and Ahuja 2006;Karthigeyan et al 2008;Sharma et al 2009). Numerous genetic diversity studies have also been conducted on tea germplasm in other regions of the world, using various molecular marker techniques (Kaundun et al 2000;Kaundun and Matsumoto 2002;Chen and Yamaguchi 2005;Matsumoto et al 2004;Ohsako et al 2008;Yao et al 2008). Most of these investigations carried out nationally or internationally, however, suffer from an important lacuna: either small sample size or accessions restricted to a particular region.…”
mentioning
confidence: 99%
“…assamica from multiple countries have revealed that collections from China and India have high levels of genetic diversity, but these studies analyzed only a few dozen accessions (Wachira et al 2001;Matsumoto 2002, 2003;Yao et al 2008). More recently, some studies analyzed several hundred germplasms using simple sequence repeat (SSR) or amplified fragment-length polymorphism (AFLP) markers (Ohsako et al 2008;Yao et al 2012;Raina et al 2012;Fang et al 2012), but only domestic germplasms in Japan, China, or India.…”
Section: Introductionmentioning
confidence: 99%